The Nordic Postmodernism : Collection : The third display of the Museum's collections. - Aarnio, Eija; Ketonen, Helka (Helsinki : KIASMA Museum of Contemporary Art, 2000)
Nordic Postmodernism, or the third display of the museum's collections brings out different aspects of the art of the 1980s and early 1990s. Post-modernism raised questions about the historicism of art, the limits of good and bad taste, the drawing of boundaries, between high and low culture, the subjectivity of the artist, and the definition of identity and gender.
Aiha, Martti ; Alalääkkölä, Sirpa ; Andersson, Jan-Erik ; Dolven, Anne Katrine ; Duncker, Maria ; Gullichsen, Alvar ; Hakola, Marikki ; Holmström, Gun ; Holopainen, Jiri ; Hukkanen, Reijo ; Kaila, Jan ; Kivinen, Markku ; Koivisto, Kaisu ; Land, Peter ; Lehtonen, Henrietta ; Liksom, Rosa ; Liulia, Marita ; Luostarinen, Leena ; Mikkola, Kirsi ; Mäki, Teemu ; Mäkilä, Jarmo ; Niskanen, Pekka ; Niva, Jussi ; Puustinen, Merja ; Rantanen, Mari ; Rantanen, Silja ; Rodtsenko-seura ; Rollof, Ulf ; Räbinä, Paavo ; Salong 3+ ; Siukonen, Jyrki ; Tomren, Anders ; Uutinen, Marianna ; Vaara, Roi ; Väisänen, Hannu
Engels
The Nordic Postmodernism : Collection : The third display of the Museum's collections, KIASMA (Museum of Contemporary Art) Helsinki, 20.1.2000 - 2001, 3th floor
boek